Resistance risk assessment within herbicide authorisation – a call for sensitivity data. Issue 2 (24th May 2012) - Ulber, Lena; Nordmeyer, Henning; Zwerger, Peter
Abstract In most European countries, the risk of herbicide resistance is assessed as part of the authorisation of herbicides in accordance with EPPO Standard PP 1/213(2). Because the susceptibility of weed populations to a certain herbicide may vary greatly, one part of resistance risk assessment is the testing for sensitivity variation among different populations of target weed species with a high resistance risk. This paper emphasises the importance of sensitivity data provision with regard to the recent EU Regulation (EC) 1107/2009 concerning the placing of plant protection products on the market and outlines the main technical requirements for sensitivity data. A useful principle is that sensitivity data should be provided for all herbicides with a high resistance risk regardless of whether resistance has already evolved against the herbicidal substance. Methodical details regarding the generation of sensitivity data are discussed, together with remaining questions that will need to be addressed if a harmonised assessment of herbicide resistance risk is to be achieved. Copyright © 2012 Society of Chemical Industry